Exclusion Methods for Managing Greenhouse Vegetable Pests - Robert C. Hochmuth; Richard K. Sprenkel (EDIS)
ENY-846, a 4-page illustrated fact sheet by R.C. Hochmuth and R.K. Sprenkel, lists several insect pest exclusion techniques for greenhouse vegetable producers in Florida. Includes references. Published by the UF Department of Entomology and Nematology, April 2008.